A intervenção arqueológica no Largo Camões - Ponte de Lima - Almeida, Carlos Alberto Brochado de (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
During the 19th century a new square was built in Ponte de Lima: the Camões Square. It was constructed in the same place were, during the Middle Ages, there was a defensive tower that protected the city’s entrance facing the Lima river bridge. That bridge dates back to the 14th century and was made to substitute another one that was constructed during the Roman Period. Nowadays, it’s still possible to see 5 arches from that roman bridge. The archaeological excavation uncovered the ruins from the Ponte de Lima’s medieval defensive system as well as two arches from the gothic bridge, and the remains of houses dating back to the 16th and the 17th century.